The Effect of Organisation Structure, Competency and Innovation on Firm Performance in The Era of Industry 4.0 - Setyani Dwi Lestari; Brantas Juwana (International Journal of Organizational Business Excellence, 2021)
The research aimed to determine the effect of organizational structure, competency, and innovation which are considered as key factors that affect firm performance in the era of industry 4.0. The research used purposive sampling survey to obtain primary data by distributing questionnaires directly to respondents or employees of Indosat Ooredoo's head office in Jakarta. The research had 135 respondents as samples. The method for data analysis was multiple regression analysis using SPSS version 25 software. The results show that the organizational structure has a positive influence of 58,6% on competency, the organizational structure has a positive influence of 44% on innovation, competency has a positive influence of 48,5% on innovation, competency has a positive effect of 72,7% on firm performance, innovation has a positive influence of 38,6% on company performance, and simultaneously both competency and innovation have a positive effect of 72,8% on firm performance. It is recommended that Indosat Ooredoo make improvements on the organizational structure to maximize employee competency and innovation to further enhance firm performance in the industry era 4.0.